2020
DOI: 10.1158/1055-9965.epi-20-0659
|View full text |Cite
|
Sign up to set email alerts
|

Daily Physical Activity and Symptom Reporting in Breast Cancer Patients Undergoing Chemotherapy: An Intensive Longitudinal Examination

Abstract: Background: Increased activity is beneficial during chemotherapy, but treatment-related symptoms may be a barrier. This study examines the relationship between daily fluctuations in symptoms and activity during chemotherapy. Methods: Women undergoing chemotherapy for breast cancer [n = 67; Mage = 48.6 (SD = 10.3)] wore an accelerometer 24 hours/day and received four text prompts/day to rate symptoms for 10 consecutive days at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Finally, each construct was measured with only a single‐item one time per day because of concerns about overburdening participants and we did not include a measure specific to barriers/facilitators (i.e., enjoyment, social support), an important SCT construct, within these analyses. However, in a prior analysis in this sample we did find common chemotherapy symptoms were related to MVPA and LPA participation 33 . Future work could examine SCT constructs at an even more microtemporal level as self‐efficacy, for example, may change even within a single day or a few hours 37 .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Finally, each construct was measured with only a single‐item one time per day because of concerns about overburdening participants and we did not include a measure specific to barriers/facilitators (i.e., enjoyment, social support), an important SCT construct, within these analyses. However, in a prior analysis in this sample we did find common chemotherapy symptoms were related to MVPA and LPA participation 33 . Future work could examine SCT constructs at an even more microtemporal level as self‐efficacy, for example, may change even within a single day or a few hours 37 .…”
Section: Discussionmentioning
confidence: 66%
“…As reported in full elsewhere, 33 participants engaged in an average of 22.74 (SD = 27.57) minutes of MVPA and 228.44 (SD = 92.64) minutes of LPA per day, both of which were relatively consistent across time point (T1: MVPA M = 22.22 [SD = 21.87], LPA M = 226.66 [SD = 81.15]; T2: MVPA M = 22.39 [SD = 26.85], LPA M = 230.41 [SD = 99.45]; T3: MVPA M = 23.78 [SD = 33.85]; LPA M = 228.36 [SD = 97.62]). Mixed models regressing treatment time point (T1, T2, and T3) and treatment status (pre‐chemotherapy dose vs.. day of/post‐chemotherapy dose) separately on MVPA and LPA revealed some differences by time point, by treatment status, and the time point by treatment–status interaction.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…They carried out ¥ maze learning training on people and found that the amplitude of group spike evoked by perforin fibers 4 hours and 24 hours after training was significantly higher than that before training. Among them, the LTP effect of people with good memory increased significantly, while the LTP effect of people with poor memory did not increase significantly [ 11 ]. Conversely, studies have shown that factors or drugs that affect LTP can also affect learning and memory processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Breast cancer patients undergoing chemotherapy had problems especially related to self-care. 3 , 4 The patient is unable to perform activity daily living which can decrease the quality of life and lead to anxiety and depression. 5 A previous study mentioned that in breast cancer patients, almost 50% of respondents need assistance from other people to fulfill their nutritional and fluid needs mobilization, toileting, bathing, and personal hygiene supervision.…”
Section: Introductionmentioning
confidence: 99%